Pneumococcal infection in patients with coeliac disease. - Thomas, H; Wotton, C; Yeates, D; Ahmad, T; Jewell, D; Goldacre, M (2008)
OBJECTIVES: Some patients with coeliac disease are hyposplenic. Splenectomy is a risk factor for pneumococcal infection. Our objective was to determine the risk of invasive pneumococcal disease - septicaemia, pneumonia or meningitis - in patients with coeliac disease. METHODS: We analysed routinely collected, linked statistical records of hospital admission to study the risk of pneumococcal infection in patients with coeliac disease, in patients who underwent splenectomy and in a comparison cohort. The main outcome measure was the rate ratio for pneumococcal infection in the coeliac and splenectomized cohorts, compared with the comparison cohort. We undertook the study using linked records in two temporally and geographically distinct populations: the Oxford region (1963-1999) and the whole of England (1998-2003). RESULTS: The rate ratio of pneumococcal infection in patients with coeliac disease was 2.06 (95% confidence interval, 1.27-3.15) in the Oxford population and 1.61 (1.36-1.90) in England as a whole. As a comparison, the rate ratios in splenectomized patients were 3.40 (2.44-4.60) and 3.32 (2.80-3.90) in the Oxford and England populations, respectively. The increased rate ratio in coeliac patients persisted beyond the first year after diagnosis of the coeliac disease. The period covered by the Oxford study was mainly before the widespread availability of pneumococcal vaccination; but the availability of pneumococcal vaccine was widespread during the time of the English study. CONCLUSION: Some patients with coeliac disease have an elevated risk of invasive pneumococcal disease.